Biomechanical analysis of backstroke start technique in swimming - Hohmann, A.; Fehr, U.; Kirsten, R.; Krueger, T. (Bewegung und Training, 2008)
This study researched in depth a 6-phase model that describes the kinematic and kinetic parameters of the backstroke start in combination with the time pattern and activity level of the mus-cles while executing the start movement. Nine male backstroke sprinters performed four backstroke starts over a distance of 7.5 m. During the start the overall start time, reaction time, wall time, flight time, and glide time were recorded. Kinetic data were measured as 3-dimensional ground reaction forces. The correlation (N = 9) of the resultant take off force and the final overall start time (7.5 m) turned out to be significant (r [9] = -.82, p = .006). Correlations were found between the times of hands off and take off (r [9] = .70, p = .04) and hands off and hip entry (r [9] = .92, p < .001). The influence of the ki-nematic and kinetic parameters of the above water phase (wall and flight activity) of the backstroke start technique is clearly shown by the analysis. EMG-data were recorded for five of the nine backstroke sprinters by a water protected 8-channel EMG from eight arm, shoulder, trunk and leg muscles. To compare the quality of muscular activity patterns, the IDANCO-system served as an adequate method. The EMG recordings in the 5 swimmers indicated a medium repetition consistency and reproducibility of the identified patterns of muscle activity. In the initial hang phase, and the final glide phase the EMG recordings of the first dolphin kick demonstrated an identical and analogue movement behavior. During the flight phase, and especially during the water entry, the number of different muscle activation patterns grew significantly.